Moringa oleifera Seed Extract Alleviates Scopolamine-Induced Learning and Memory Impairment in Mice - Zhou, Juan; Yang, Wu-shuang; Suo, Da-qin; Li, Ying; Peng, Lu; Xu, Lan-xi; Zeng, Kai-yue; Ren, Tong; Wang, Ying; Zhou, Yu; Zhao, Yun; Yang, Li-chao; et al. (Frontiers in Pharmacology, 2018)
The extract of Moringa oleifera seeds has been shown to possess various pharmacological properties. In the present study, we assessed the neuropharmacological effects of 70% ethanolic M. oleifera seed extract (MSE) on cognitive impairment caused by scopolamine injection in mice using the passive avoidance and Morris water maze (MWM) tests. MSE (250 or 500 mg/kg) was administered to mice by oral gavage for 7 or 14 days, and cognitive impairment was induced by intraperitoneal injection of scopolamine (4 mg/kg) for 1 or 6 days. Mice that received scopolamine alone showed impaired learning and memory retention and considerably decreased cholinergic system reactivity and neurogenesis in the hippocampus. MSE pretreatment significantly ameliorated scopolamine-induced cognitive impairment and enhanced cholinergic system reactivity and neurogenesis in the hippocampus. Additionally, the protein expressions of phosphorylated Akt, ERK1/2, and CREB in the hippocampus were significantly decreased by scopolamine, but these decreases were reversed by MSE treatment. These results suggest that MSE-induced ameliorative cognitive effects are mediated by enhancement of the cholinergic neurotransmission system and neurogenesis via activation of the Akt, ERK1/2, and CREB signaling pathways. These findings suggest that MSE could be a potent neuropharmacological drug against amnesia, and its mechanism might be modulation of cholinergic activity via the Akt, ERK1/2, and CREB signaling pathways.